An inquiry into the progress and present condition of mechanics' institutions. Part I - Leslie, T.E. Cliffe (Statistical and Social Inquiry Society of Ireland, 1852)
The formation and development of Mechanics' Institutions may be regarded as characteristic social features of the present century, the first association of this description having been established at Birmingham in 1796, under the title of the "Birmingham Brotherly Society."
Read February 16th 1852
Keywords: Mechanics' institutes; Adult education; 314.15